Respiratory allergy caused by house dust mites: What do we really know? - Calderón, Moisés A.; Linneberg, Allan; Kleine-Tebbe, Jörg; De Blay, Frédéric; Hernandez Fernandez de Rojas, Dolores; Virchow, Johann Christian; Demoly, Pascal (Journal of allergy and clinical immunology, 2015)
The house dust mite (HDM) is a major perennial allergen source and a significant cause of allergic rhinitis and allergic asthma. However, awareness of the condition remains generally low. This review assesses the links between exposure to HDM, development of the allergic response, and pathologic consequences in patients with respiratory allergic diseases. We investigate the epidemiology of HDM allergy to explore the interaction between mites and human subjects at the population, individual, and molecular levels. Core and recent publications were identified by using “house dust mite” as a key search term to evaluate the current knowledge of HDM epidemiology and pathophysiology. Prevalence data for HDM allergen sensitization vary from 65 to 130 million persons in the general population worldwide to as many as 50% among asthmatic patients. Heterogeneity of populations, terminology, and end points in the literature confound estimates, indicating the need for greater standardization in epidemiologic research. Exposure to allergens depends on multiple ecological strata, including climate and mite microhabitats within the domestic environment, with the latter providing opportunity for intervention measures to reduce allergen load. Inhaled mite aeroallergens are unusually virulent: they are able to activate both the adaptive and innate immune responses, potentially offering new avenues for intervention. The role of HDM allergens is crucial in the development of allergic rhinitis and asthma, but the translation of silent sensitization into symptomatic disease is still incompletely understood. Improved understanding of HDMs, their allergens, and their microhabitats will enable development of more effective outcomes for patients with HDM allergy.